The Economic Effects of Energy Price Shocks - Kilian, Lutz (Journal of Economic Literature, 2008)
Large fluctuations in energy prices have been a distinguishing characteristic of the U.S. economy since the 1970s. Turmoil in the Middle East, rising energy prices in the United States, and evidence of global warming recently have reignited interest in the link between energy prices and economic performance. This paper addresses a number of the key issues in this debate: What are energy price shocks and where do they come from? How responsive is energy demand to changes in energy prices? How do consumer's expenditure patterns evolve in response to energy price shocks? How do energy price shocks affect U.S. real output, inflation, and stock prices? Why do energy price increases seem to cause recessions but energy price decreases do not seem to cause expansions? Why has there been a surge in the price of oil in recent years? Why has this new energy price shock not caused a recession so far? Have the effects of energy price shocks waned since the 1980s and, if so, why? As the paper demonstrates, it is critical to account for the endogeneity of energy prices and to differentiate between the effects of demand and supply shocks in energy markets when answering these questions.